Aranykalyiba . Golden Hut: A Year with Emilke Karácsony in the Hidegség of Gyimes - Zsigmond, Dezső (Hungary, 2003)
Duration: 00:55:00 Thirteen-year-old Emilke, who is similar to Ábel (the protagonist of a famous novel about a young boy living in the mountains of Transylvania – transl.), lives in his mountain hut in a place called Hidegség in Gyimes, Transylvania. From early spring to the first snowfall he grazes cows, makes cheese from the milk, and only sees his parents when one or the other goes up to the mountain pasture and takes the cheese home. These meetings are rare and short. The only companions for the boy are the cows and the dogs, since he has to climb one or two hills just to get to the closest neighbour. The hours, days, weeks, spring, summer, and autumn melt into each other in this solitude…